A Legal (And Otherwise) Realist Response to “Sex as Contract” - Fineman, Martha Albertson (Columbia Journal of Gender and Law, 1994)
The serious suggestion made in the article “Sex as Contract: Abortion and Expanded Choice” that society use the legal coercion of “contract” to give definition to the social and emotional experience of “sex” provides evidence for the feminist assertion that there are often explicit but unconsidered gendered consequences attached to the implementation of so- called “neutral” legal concepts and doctrine. “Contract” may be a neutral term, but, given the different social and cultural “realities” women and men experience in our society, sex and reproduction are very gendered acts. The assertion that law all too typically has been oblivious to gendered consequences is related to the empirical observation that the law, both institutionally and doctrinally, systemically favors men and male experiences. Perhaps this bias is not surprising given the fact that women are relatively new to the legal profession and still are not found in large numbers among those who create and define policy and law. However, one area where male bias has been at least restrained by limited but explicit considerations of gendered experience is in the area of reproductive choices. The Supreme Court in Roe v. Wade and Danforth recognized that pregnancy and the social consequences of reproduction are unequally gendered experiences and consequentially it allocated the abortion decision to women. As the Danforth court noted: Inasmuch as it is the woman who physically bears the child and who is the more directly and immediately affected by the pregnancy, as between [the woman and her male partner], the balance weighs in her favor. These initial observations are relevant because the authors of “Sex as Contract” are particularly concerned with which partner to a reproductive event will ultimately control the abortion decision. The authors do not explicitly discuss gender as affecting either abortion or the “economics of contract law”—the method they designate as appropriate for allocation of decision-making. But a consideration of the gendered implications of a contract analysis is essential for an assessment of its fairness because ultimately this article seems little more than a thinly disguised attempt to reassert male-biased rules under the cloak of so-called “neutral” principles.